Word Order and Prosodic‐Structure Constraints in Tagalog. (10th October 2013) - Sabbagh, Joseph
Abstract This paper is concerned with two apparently unrelated word‐order facts in Tagalog: In interrogative sentences, fronted wh‐phrases follow the complementizer (Comp–WhP order), and in both interrogative and noninterrogative sentences, the subject follows the verb (verb‐initial order). It is argued that neither of these word orders reflects a word order that is expected on the basis of the syntactic structure alone. Instead, a unified explanation for these word orders is proposed, according to which they arise as the result of a lowering operation that applies at Phonological Form (PF) and is prosodically driven. Specifically, lowering applies in order to satisfy a prosodic‐structure constraint, Weak Start, which requires elements that are relatively high on the prosodic hierarchy to be preceded by elements that are equal to or lower than them on the prosodic hierarchy. The word orders discussed herein therefore involve a mismatch between syntax and phonology, and lowering provides a means by which syntactic principles as well as principles relating to prosodic‐structure can be simultaneously upheld.